1895
DOI: 10.1007/bf02124930
|View full text |Cite
|
Sign up to set email alerts
|

Ueber arithmetische Eigenschaften analytischer Functionen

Abstract: die ~unkte einer beliebigen a b z ~ h l b a r e n _Punktmenge im Gebiete der unbeschrgnkt ver~inderlichen complexen G-r6sse x be~eichnen, wghrend Q irgend eine in dieser •bene i~b e r a l l d i c h t e Tunktmenge bedeuten sell. Dann giebt es stets unendlivh viele e i n d e u t i g e a n a t y t i s c h e t P u n c t i o n e n f (s) , die fi~r aT, le Argumente xo, xi, 9 9 9 tier Menge t ~ nut Werthe aus der Menge Q annehmen. B e w eis. Man bilde die ganzen ralionalen Funetionen: 9 o(X) = 1 , ~t (x)-= s-So, ~(x)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

1902
1902
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 0 publications
0
33
0
4
Order By: Relevance
“…Stäckel (Stäckel, 1893) showed that in the case of orthogonal coordinates the geodesic Hamilton-Jacobi is separable if and only if…”
Section: Riemannian Metric and Orthogonal Coordinatesmentioning
confidence: 99%
“…Stäckel (Stäckel, 1893) showed that in the case of orthogonal coordinates the geodesic Hamilton-Jacobi is separable if and only if…”
Section: Riemannian Metric and Orthogonal Coordinatesmentioning
confidence: 99%
“…Gravitational potentials with explicitly known second integrals of motion are rare, the most frequently used in astronomy are axisymmetric potentials and also Stäckel (1893) potentials 1 that cover a large class of potentials, but are not always sufficiently realistic. Such explicit forms are useful, for instance, to understand more clearly the underlying physics of dynamical systems, to build stationary distribution functions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…With a smooth real function V ͑potential energy͒ on a Riemannian manifold (Q n ,g) ͑configuration manifold͒ we associate two differential equations, the time-independent Hamilton-Jacobi equation 1 2 ٌW•ٌWϩVϭE, ͑1.1͒…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Theorem 1.1: ͑Stäckel, 1893͒ The Hamilton-Jacobi equation is separable in orthogonal coordinates q គ if and only if the diagonal components g ii of the metric tensor and the potential V have the form It happens that for solutions of this kind, Eqs.…”
Section: Introductionmentioning
confidence: 99%